2011
DOI: 10.1111/j.1601-0825.2011.01791.x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of medical interventions for oral submucous fibrosis and future research opportunities

Abstract: Oral submucous fibrosis (OSF) is a chronic, insidious disease caused by areca nut use, and is associated with both significant morbidity (including pain and reduced oral opening) and an increased risk for malignancy. This systematic review explored and updated the current medical (i.e., non-surgical) interventions available for the management of OSF. Of the 27 published medical interventions, there were four randomized controlled trials. The overall quality of these randomized controlled studies was assessed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
177
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(179 citation statements)
references
References 50 publications
1
177
1
Order By: Relevance
“…There is paucity of literature on QoL assessment in OSF patents 9 in spite of its higher prevalence 2,3 and malignant potential. 2 This might be due to unavailability of a condition-specific QoL measure for OSF.…”
Section: 5005/jp-journals-10024-2262mentioning
confidence: 99%
“…There is paucity of literature on QoL assessment in OSF patents 9 in spite of its higher prevalence 2,3 and malignant potential. 2 This might be due to unavailability of a condition-specific QoL measure for OSF.…”
Section: 5005/jp-journals-10024-2262mentioning
confidence: 99%
“…Conclusive evidence now exists indicating that OSMF is caused by chronic irritation of mucosa with arecanut, a masticatory substance used predominantly by peoples of South and SouthEast Asian ethnicity. 1,4 Although arecanut is attributed to cause OSMF, it is not understood why all arecanut chewers do not suffer from this disease. It is also observed that maximum changes are seen in areas of oral cavity bathed with saliva which raises the suspicion that some other factors in saliva of the patients may influence the disease process.…”
Section: Introductionmentioning
confidence: 99%
“…Several other descriptive terms have been attributed; submucosal fibrosis of palate and pillars, diffuse oral submucous fibrosis idiopathic scleroderma of the mouth, idiopathic palatal fibrosis and sclerosing stomatitis. 1 It is characterized by a juxtaepithelial inflammatory reaction followed by fibroelastic change in the lamina propria and associated epithelial atrophy. This leads to a restricted mouth opening, resulting as trismus leading to restriction of food consumption, difficulty in maintaining oral health as well as impairs the ability to speak.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown that antioxidants are highly effective in controlling the signs and symptoms of OSMF and have been the mainstay of a conservative approach for management of OSMF. [4] [5] Several narrative and systematic reviews on management of OSMF have highlighted the beneficial role of various antioxidants like natural extracts, micronutrients, vitamins, nutritional supplements. [5][6] [7] Nonetheless, no systematic review or meta -analysis has yet given evidence of efficacy of systemic Antioxidants in management of OSMF.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%
“…[4] [5] Several narrative and systematic reviews on management of OSMF have highlighted the beneficial role of various antioxidants like natural extracts, micronutrients, vitamins, nutritional supplements. [5][6] [7] Nonetheless, no systematic review or meta -analysis has yet given evidence of efficacy of systemic Antioxidants in management of OSMF. Thus, this systematic review aimed to critically summarize and evaluate results of clinical studies investigating systemic antioxidants to improve signs and symptoms of OSMF.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%